Development and validation of the activities and participation children and adolescents -neck (APCAN) measure - Devashish Tiwari; Keshrie Naidoo; Emily Z. Eddy; Naseem Chatiwala; Maninderjit Kaur (SpringerOpen, 2023)
Abstract Background Neck pain is the fourth leading cause of years lost to disability in children warranting a comprehensive assessment of neck pain and its impact on activities and participation. Hence, the purpose of this study was to develop a new measure (i.e., Activities and Participation Children and Adolescents -neck [APCAN]) specific to evaluating activity limitation and participation restrictions in children and adolescents and to establish its content validity. Methods Development and content validation of the APCAN was completed in four steps: (1) item development, (2) item evaluation by content experts, (3) content validity calculation, and (4) cognitive testing via interviews to ensure readability and comprehension of the items on the APCAN. Results An initial pool of 52 items was created that was revised to 20 items after modified Delphi process and cognitive interviews. Each item was rated on a 0-10 numeric rating scale (0 = not difficult at all, 10 = extremely difficult) with higher scores indicating higher perceived disability secondary to neck pain. All 20 items retained the content validity ratio critical value and the overall content validity index was 0.88 indicating excellent content validity. Conclusion The APCAN provides an easy to use, comprehensive assessment of functional limitations associated with neck pain in children.